2016
DOI: 10.1097/ppo.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Physical Activity in Patients With Colorectal Cancer

Abstract: Colorectal cancer (CRC) is a leading cause of cancer incidence and mortality in the U.S. Notwithstanding major improvements in the early detection and treatment of CRC, an important proportion of patients diagnosed with localized disease ultimately recur and die, underscoring the need of new therapeutic approaches. Vitamin D and physical activity (PA) have emerged as two potential interventions for both prevention and treatment of CRC. Plausible biological mechanisms have been described for the anti-neoplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…We identified a statistically significant dose-response relationship in breast cancer between patient survival and circulating levels of 25-OH-D. A protective effect of higher vitamin D levels have also been shown in skin cancer, 48 ovarian cancer, 49 prostate cancer, 50 and colorectal cancer. 51 As shown in Table 1 and Figure 3 , the linear relationship encompasses vitamin D levels from 23.3 to 187.5 nmol/L. It should be noted that due to limited data presented in the studies the highest 3 vitamin D levels (187.5, 121.5, and 94.1 nmol/L) were all estimated and therefore the linear relationship at higher levels of vitamin D are likely to be unreliable.…”
Section: Discussionmentioning
confidence: 94%
“…We identified a statistically significant dose-response relationship in breast cancer between patient survival and circulating levels of 25-OH-D. A protective effect of higher vitamin D levels have also been shown in skin cancer, 48 ovarian cancer, 49 prostate cancer, 50 and colorectal cancer. 51 As shown in Table 1 and Figure 3 , the linear relationship encompasses vitamin D levels from 23.3 to 187.5 nmol/L. It should be noted that due to limited data presented in the studies the highest 3 vitamin D levels (187.5, 121.5, and 94.1 nmol/L) were all estimated and therefore the linear relationship at higher levels of vitamin D are likely to be unreliable.…”
Section: Discussionmentioning
confidence: 94%
“…Evidence shows that the vitamin D levels are inversely associated with CRC risk and positively associated with improved overall and CRC-specific survival ( Morales-oyarvide et al, 2016 ). Vitamin D and its nuclear transcriptional receptor VDR have chemo-prevention activities for CRC ( Aggarwal and Kallay, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies in vitro demonstrated the efficacy of 1,25(OH) 2 D 3 in contrasting the EMT triggered by TGF-β, due to the inhibited expression of EMT markers and the decreased migration and invasion of epithelial and ovarian cancer cells [6][7][8][9][10]. The clinical studies that have evaluated the efficacy of vitamin D supplementation have described a role merely preventive in cancer formation and progression, whereas there are no evidences for curative properties on malignant tumors [11][12][13].…”
Section: Introductionmentioning
confidence: 99%